Voriconazole-induced QT interval prolongation and ventricular tachycardia: a non-concentration-dependent adverse effect - Alkan, Yoav; Haefeli, Walter E.; Burhenne, Jürgen; Stein, J.; Yaniv, I.; Shalit, Itamar (Clinical infectious diseases, 2004)
A 15-year-old patient with acute lymphoblastic leukemia and Fusarium infection was treated with voriconazole. She developed asymptomatic bradycardia, QT interval prolongation, and nonsustained, polymorphic ventricular tachycardia, which recurred upon rechallenge with the drug. Voriconazole levels and metabolism were within expected normal values. This non—concentration-dependent, voriconazole-associated ventricular tachycardia mandates cardiac rhythm monitoring during voriconazole treatment.